The anti-obesity effects of a water-soluble glucan from Grifola frondosa via the modulation of chronic inflammation - Jiang, Xue; Hao, Jie; Zhu, Yanfeng; Liu, Zijian; Li, Lanzhou; Zhou, Yulin; Li, Yu; Teng, Lirong; Wang, Di (Frontiers in Immunology, 2022)
Polysaccharides from Grifola frondosa (G. frondosa) have anti-obesity and anti-inflammatory activities. In this study, the major type, molecular weight, homogeneity and structure of a polysaccharide purified from G. frondosa (denoted GFPA) were determined. In high-fat diet (HFD)-treated mice, 8 weeks of GFPA administration efficiently decreased body weight and blood glucose concentration and counteracted hyperlipidemia. GFPA efficiently decreased adipocyte size and ameliorated inflammatory infiltration in the three types of white adipose tissue and alleviated steatosis, fat accumulation and inflammatory infiltration in the livers of HFD-fed mice. GFPA also decreased the concentrations of aspartate aminotransferase, alanine aminotransferase and pro-inflammatory factors in the sera and livers of HFD-treated mice. Furthermore, GFPA was found to regulate lipid metabolism via the inhibition of ceramide levels in HFD-treated mice. GFPA exhibited strong anti-obesity effects via the modulation of chronic inflammation through Toll-like receptor 4/nuclear factor kappa-B signaling, which supports the use of GFPA for the treatment of obesity.